Ipsipulsion: A forgotten sign of lateral medullary syndrome - Paliwal, Vimal Kumar (Ann Indian Acad Neurol, 2015)
Ipsipulsion is a clinical sign specifically seen in lateral medullary syndrome. It is characterized by two involuntary phenomenons. One is static eye deviation ipsilateral to the side of lesion especially in the absence of visual fixation. Second is the saccadic lateropulsion whereby voluntary saccades towards the side of lesion are hypermetric and saccades towards opposite side are hypometric. The vertical saccades may also appear oblique. Ipsipulsion is produced due to damage to the contralateral olivocerebellar pathways that crosses midline in medulla and pass through the ipsilateral inferior cerebellar peduncle to supply ipsilateral cerebellar hemisphere.